Integrity challenges in harsh environments: lessons learned and potential development strategies - Faisal Khan; Ahmed, S; Hashemi, SJ; Yang, M; Caines, S; Oldford, D (2014)
Vast reserves in the Arctic and sub-Arctic regions have attracted interest of the oil and gas industry. However, oil and gas development in harsh environments faces significant technical and logistical challenges. A workshop on "safety and integrity management of operations in harsh environments" was organized by the Safety and Risk Engineering Group at Memorial University of Newfoundland focusing on main aspects of asset integrity. The event featured representatives from industry, regulatory authorities, and research and development institutions. Participants shared experience and lessons learned, and together developed a roadmap for achieving desired solutions. This paper briefly reviews the lessons learned from the two-day workshop and shares recent developments and applications of risk-based approaches to degradation modeling, integrity assessment, and inspection and maintenance decision-making in harsh environments. The recently developed novel approach of risk-based winterization method is introduced. This approach helps to analyze how much winterization is sufficient to address local and regional weather loading considering operating envelop and criticality of the components or the system. A case study from the Arctic region is used for discussion.